The Grounded Theory Perspective: Human Resource’s Characteristics In Supporting Risk-Based Management Implementation - Aviani Widyastuti; Mudrifah Mudrifah (Universitas Muhammadiyah Malang, 2020)
This study aims to develop employee organizations' role in implementing risk management in public sector organizations. This study's character uses several indicators, including values, attitudes, interests, and religion. The research was conducted at public sector organizations in the non-profit category, Infaq Amal Zakat and Shodaqoh Muhammadiyah (LAZISMU) in Malang City. The research method used is grounded theory research with a qualitative approach, in which data research uses structured and open interview techniques. The collected data will be analyzed using grounded theory analysis techniques. The study results found several factors, as seen from their abilities, values, attitudes, interests, and religiosity, in supporting the implementation of risk management in Malang. These characteristics include working with time, the right placement of human resources, mastery of job descriptions, information, ability, and transfer of knowledge, in terms of values, including cooperation, responsibility, democracy, solidarity, humanity, honesty, order, and discipline. In terms of attitude, including being wise, with integrity, cooperative, open, and selective. In terms of interest, it is shown by being participatory, actualizing, and proactive.Meanwhile, in terms of religiosity, it includes the mandate to carry out duties, desire in preaching, and personal needs to fill charity activities with full volunteerism.